Diglossic switching by the Pre-school Children. : The Case of ‘Dib Tahar’ Primary School - Mouleme, Manel (Journal of Human Sciences, 2020)
The present study aims at investigating children’s switching between Modern Standard Arabic and Algerian Arabic. To reach this aim, an ethnographic approach is followed with pre-school children aging six years old at ‘Dib Tahar’ primary school at Elkroub, Constantine- Algeria. It is based on triangulation: participant observation, recordings, and an interview with the teacher of the sample. The results reveal that pre-school children do switch between the varieties of Arabic in the class and they may deviate from the standard pronunciation of the Algerian words to express themselves. Intra-word switching is very common in their speeches.Further, Children’s switching is rule-governed. The results obtained challenge Ferguson’s definition of diglossia and call for reconsidering the separation of its domains.